Human equilibrative nucleoside transporter 1 (hENT1): do we really have a new predictive biomarker of chemotherapy outcome in pancreatic cancer patients? - Mohelnikova-Duchonova, Beatrice; Melichar, Bohuslav (Pancreatology, 2013)
Although systemic chemotherapy significantly improves the overall survival of pancreatic cancer patients, the prognosis remains extremely poor. The development of a drug resistance, either de novo or induced resistance, significantly limits the effectiveness of chemotherapy. SLC29A1 gene encodes human equilibrative nucleoside transporter 1 (hENT1) protein that is mediating the transport of nucleotides, both purines and pyrimidines, into the tumor cells. The aim of this mini-review is to summarize the current information concerning the prognostic and predictive role of SLC29A1 transporter (hENT1) expression in pancreatic cancer. Increased expression of SLC29A1 in vitro has been described as a potential critical factor determining the sensitivity of pancreatic cancer cells to gemcitabine and 5-fluorouracil, the principal cytotoxic agents used in the treatment of pancreatic cancer. The reports on the relationship between SLC29A1 expression and prognosis of patients with pancreatic cancer are currently rather conflicting. However, majority of studies on patients with resected pancreatic cancer have suggested that high SLC29A1expression may be predictive of improved survival in patients treated with gemcitabine. SLC29A1 has not been shown to represent a predictive biomarker for patients treated by 5-fluorouracil. In conclusion, potential prognostic and predictive role of SLC29A1 has been demonstrated for selected subset of patients.
Keywords: deoxycytidin; nádory slinivky břišní; Humans; Antimetabolites, Antineoplastic; Biomarkers, Tumor; Antineoplastic Agents; hENT1; lidé; Gemcitabine; Equilibrative Nucleoside Transporter 1; gemcitabin; nádorové biomarkery; SLC29A1; Pancreatic Neoplasms; Deoxycytidine; prognóza; protinádorové antimetabolity; protinádorové látky; ekvilibrační přenašeč nukleosidů 1; Pancreatic cancer; Membrane transport protein; Prognosis